REPAIR OF SCIATIC NERVE LESION AUGMENTED WITH AMNION MEMBRANE COMPOSITE AND MESENCHYMAL STEM CELL - Heri Suroto; R. Taufan Mulyo Wibisono (Journal Orthopaedi and Traumatology Surabaya, 2020)
Background: Peripheral nerve injuries (PNI) are quite common, with an incidence of 13.9% per 100,000 people per year. The most cause is direct penetrating trauma. PNI will cause a significant decrease in the quality of life of patients. Case: A 21-years-old woman complained of the inability to move her right leg and numbness. She had been injured in the of the right thigh due to broken glass. The patient underwent emergency surgery to repair the right Femoral artery and the Sciatic nerve. Discussion: After six months since the first operation, flail foot and anesthesia were persisting with a FADI score of 47.1. We decided to perform re-exploration, from the exploration we found neuroma on the sciatic nerve. Excision was performed on the Neuroma then an end-to-end anastomosis was performed on both sciatic nerve components (tibial and peroneal) and augmented using amniotic membrane composites and mesenchymal stem cells. After 6 months since the second surgery, the patient could perform ankle dorsal flexion. After 12 months postoperatively, the patient could move his right leg functionally, sensory function also improved. Patients can undergo daily activities without difficulty, with a FADI score of 96.2. Conclusion: There is a significant improvement in the patient's foot function after surgery using the method we used, more research is needed to optimize the use of amniotic membrane and mesenchymal stem cells as augmentation in nerve repair.